2022
DOI: 10.1186/s40001-022-00662-7
|View full text |Cite
|
Sign up to set email alerts
|

Early infant feeding and allergic respiratory diseases in Ibb city, Yemen

Abstract: Background Allergic respiratory diseases (ARD) are a highly prevalent health problem affecting infants and children in Yemen. Early infant feeding predisposition to the development of ARD has been a controversial question. The aim of this study is to investigate the association between early feeding before 6 months of age and the development of ARD among children attending Childhood and Maternity Public Hospital (CMPH), Ibb, Yemen Republic. Subjects and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This implies that breastfeeding can either protect against or at least diminish the risk of asthma in children. A similar pattern was observed in a study by Obaid et al (2022) in Yemen, where infants given formula before six months were more susceptible to asthma attacks than those who were breastfed. Furthermore, breastfeeding contributes to enhanced intelligence in children.…”
Section: A Mother's Shield: Countering Various Diseases With the Powe...supporting
confidence: 85%
“…This implies that breastfeeding can either protect against or at least diminish the risk of asthma in children. A similar pattern was observed in a study by Obaid et al (2022) in Yemen, where infants given formula before six months were more susceptible to asthma attacks than those who were breastfed. Furthermore, breastfeeding contributes to enhanced intelligence in children.…”
Section: A Mother's Shield: Countering Various Diseases With the Powe...supporting
confidence: 85%
“…The risk of bias in randomized controlled trial (RCT) studies was assessed using the Cochrane Collaboration Risk of Bias tool [ 21 ], and the risk of bias in non-RCT trials was assessed using the Risk of Bias in Nonrandomized Studies of Interventions tool [ 22 ]. For all study reports, the summary Tables ( Supplemental Tables 1 and 2 ) [ [8] , [9] , [10] , [11] , [13] , [14] , [15] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] ,…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of 9 studies (55,302 participants) showed no significant association between the timing of complementary foods introduction and asthma (OR, 0.98; 95% CI: 0.92, 1.04; P = 0.52; moderate heterogeneity [I 2 = 31%], Supplemental Figure 8A ) [ 45 , 48 , 55 , 65 , 79 , [81] , [82] , [83] , 89 ]. Subgroup analyses of the time points (<3 mo compared with <4 mo compared with <6 mo) ( Supplemental Figure 8B ) [ [45] , [48] , [55] , [65] , [79] , [81] , [82] , [83] , [89] ] of complementary food introduction or the end points (0–3 compared with 3–6 compared with 6–12 y) of the outcome assessment ( Supplemental Figure 8C ) [ [48] , [55] , [65] , [79] , [81] , [82] , [83] , [89] ] showed that early introduction of complementary foods was not a protective factor for reduced risk of asthma in the future.…”
Section: Risk Of Asthmamentioning
confidence: 99%